Islamic music listening, spiritual well-being and burnout of employees in Islamic university - Mohamad Shariff, Nurasikin; Azhar, Nor Atiqah; Abu Bakar, Siti Nurbayani; Ahmad, Azmir; Kaderi, Mohd Arifin; Saidi, Sanisah (Penerbit KUIS, 2022)
In Malaysia, working in university with Islamic vibes that boost the spiritual well-being and less burnout need to be supported with empirical evidence. The aim of the study is to examine the relationship between listening to Islamic music, the spiritual wellbeing, and burnout of employees in public university. A crosssectional study using online survey was conducted among 140 employees in a public university during the Covid-19 movement control order in Malaysia (April to May 2021). The set of questionnaires include socio-demographic data, the types and frequency of music listened by the employees, Modified Maslach Inventory Burnout (MBI), the Duke University Religion Index (DUREL) and spiritual well-being (SWB). The data was analysed using SPSS version 26.0, and hypotheses were tested using MannWhitney U test, Kruskal Wallis and Spearman correlation. Majority of employees listened to music every day and 51.4% of study participants listened to Islamic music or audio. The study participants have high level of religiosity (DUREL Mean = 24.02, SD=±2.352), high spiritual well-being (SWB) (Mean= 109.84, SD=±9.014). For the burnout category, there was low level of depersonalization (Mean= 8.54, SD=±5.728), moderate emotional exhaustion (Mean=20.51, SD=±9.866), and high personal accomplishment (Mean=31.87, SD=±7.956) among employees. SWB correlates positively with personal accomplishment and negatively with emotional exhaustion and depersonalisation (p<.05). The present study highlights that listening to Islamic type of music that potential support the mental well-being and productivity of employees.